(untitled) (Indian Journal of Arid Horticulture, 2013)
Ber (Zizyphus mauritiana Lamk.) occupies as an important fruit crop of arid and semi-arid region and its plantation is increasing gradually every year in India. Its cultivation on marginal land with poor soil conditions can give very good revenues with less input. However, the major constraints in higher production are attack of diseases and it has been observed that some of the diseases (leaf spot and fruit rot) and post harvest diseases are concern with productivity and economic yield in this crop.